Analisis Pengaruh Citra Merek, Persepsi Harga, dan Persepsi Kualitas Produk Terhadap Keputusan Pembelian (Studi Pada Konsumen produk ATBM Pekalongan) - Iryanita, Rizky; Sugiarto, Yohannes (Faculty of Economics and Business Diponegoro University, 2013)
In this research, the problem encountered by Pekalongan ATBM product is a lack of people’s interest in buying ATBM products because the products stagnated or not developed. Lack of people’s interest in buying decision thought to be caused by several things, like lack of brand image that still clings to every products of ATBM, incompability of the pricing on the product ATBM, and lack of people’s knowledge about quality of the products in ATBM Pekalongan, so that makes the production of ATBM in several SMES Pekalongan declined during the last 3 years. The purpose of this research was to analyze the influence of brand image on buying decision, price perception on buying decision, and product quality perception on buying decision. And to analyze the dominant factor which influence buying decision of ATBM in Pekalongan. The collection of data in this research was conducted by questionnaires method to 60 ATBM respondents in Pekalongan. The techniques which used are Probability Sampling technique to determine the responses of respondents to brand image variable, price perception, perception of product quality and buying decision using Simple Random Sampling approach,. The analysis techniques used in the research are validity test, reliability test, classic assumptions test, linear regression analysis and hypothesis test including the t test, F test, and coefficient of determination. The research results showed that the independent variables such as brand image, price perceptions, and product quality perception give significant and positive effect on the dependent variable is buying decision. The most dominant variable in influencing buying decision is product quality perception variable and the least affect is price perception variable.